2020
DOI: 10.29406/jmm.v16i1.2078
|View full text |Cite
|
Sign up to set email alerts
|

Kinerja Kewirausahaan: Faktor-Faktor Pendorong Usaha Kecil dan Menengah (UKM)

Abstract: Tujuan dari penelitian ini adalah untuk menentukan apakah ada hubungan antara nilai-nilai wirausaha dan kinerja kewirausahaan pada sektor ekonomi informal serta apakah motivasi karyawan memediasi hubungan tersebut. Survei dilakukan di Kota Pangkalpinang, Provinsi Kepulauan Bangka Belitung menggunakan kuesioner terstruktur dengan jumlah sampel sebesar 351 responden melalui teknik convenience sampling pada Usaha Kecil dan Menengah (UKM). Uji hipotesis dilakukan dengan cara Structural Equation Model (SEM) menggun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…Companies can gain insight into employees' experiences and attitudes toward their work by monitoring and measuring employee engagement, motivation, and satisfaction. This information can be used to identify areas where improvements can be made and to develop targeted interventions to improve employee retention [22], [29]. For example, if employees report low levels of engagement, companies can explore ways to increase employee engagement in the decision-making process or provide professional development and career advancement opportunities.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Companies can gain insight into employees' experiences and attitudes toward their work by monitoring and measuring employee engagement, motivation, and satisfaction. This information can be used to identify areas where improvements can be made and to develop targeted interventions to improve employee retention [22], [29]. For example, if employees report low levels of engagement, companies can explore ways to increase employee engagement in the decision-making process or provide professional development and career advancement opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…Research has identified several factors that influence employee satisfaction, including job characteristics, organizational culture, leadership, and social support [12], [22], [23], [29], [52], [53]. Job characteristics, such as task variation, autonomy, and feedback, were found to have a positive relationship with employee satisfaction [28], [33], [54], [55].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 3 more Smart Citations